Evaluación de la eficiencia de una batería de filtros empacados en zeolita en la remoción de metales pesados presentes en un licor mixto bajo condiciones de laboratorio (2011)
This article shows the research results on the removal of five heavy metals (lead, nickel, chromium, cadmium and mercury) present in a liquor made of a mixture of wastewater from San Fernando wastewater treatment plant and a solution prepared with known concentrations of heavy metals, using a series of batery filters packed with zeolita clinoptilolita. The experiments were run under controlled conditions of flow and pH, at room temperature. It was found that the removal efficiency was significantly high under the specified design conditions; also, it was found an important removal of the contaminants after passing through the filters, independently of the initial concentration, with the highest observed removal for mercury.